Organization оf Electrochemical Protection оf Steel Underground Pipelines Against Corrosionin the Gas Distribution Industry of the Republic of Belarus - N. V. Strutsky; V. N. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2024)
Steel underground gas pipelines occupy a significant share of the total length of gas distribution pipelines,  and therefore their maintenance in proper condition is a constant and very urgent task. Due to its global nature, the main influencing factor affecting the technical condition of any steel underground pipelines, including gas pipelines, is corrosion, primarily soil corrosion. To protect against it on pipeline networks, along with insulating coatings, electrochemical protection (ECP) is applied, that is, following the definition of STO [Standard of Organization] 17330282.27.060.001–2008,  protection of metal against corrosion in an electrolytic environment, carried out by establishing a protective potential on it or eliminating the anodic potential shift from the stationary potential. In the gas distribution industry of the country, methods and means of electrochemical protection have been applied since the beginning of gasification and the construction of the first gas pipelines. All gas supplying organizations of the State Production Association for Fuel and Gasification “Beltopgaz” (six regional and Minsk city), which operate gas distribution facilities, have specialized corrosion protection services. These services provide maintenance of available ECP equipment, conduct electrical measurements on gas pipelines and corrosion studies of soils, and have certified laboratories. This paper is devoted to the analysis of domestic experience in organizing electrochemical protection of steel underground gas distribution pipelines, searching for promising directions for its improvement and increasing efficiency through the implementation of a unified industry technical policy, automation and telemechanization of ECP equipment in the general context of digital transformation, optimization of the timing and volume of maintenance.